گانگوی خاندان کے علماء ،مشائخ او ر شعراء کی مذہبی اور سماجی خدمات ؛ ایک تاریخی جائزہ: Religious and social Contributions of scholars, Mashaikh and poets of the Gangvi family; A historical overview - Mustafa, Dr. Ata-ul-; Mustafa, Raza-ul- (Al-Amīr Research Journal for Islamic Studies, 2023)
Gangvi is the name of a family of ulama, scholars and poets in Mianwali. The ancestors of the Gangvi family migrated from Baghdad and settled in these areas. Because of the family’s origin as a Sayyid family it has been a noble family. Most family members have been important and influential Islamic scholars in their local area. Among the Gangvi Ulama, Syed Ahmad uddin Gangvi became the most famous. He was indeed a great scholar and a mystic of his time. He remained affiliated with Fiqh and its teachings effectively for a long period of 85 years. Being a scholar of such a status and magnitude Syed Ahmad served as the Great Mufti (Al Mufti al Azam) at Sial Shareef. He Authored books in Arabic, Persian, Urdu, Punjabi and Saraiki with equal skill and wisdom. Most of his works is available in manuscripts. All of his books reflect his scholarly wisdom and intellect and indicate his great achievements. It is a fact that this family is also the founder of the scholarly tradition in Mianwali. Some scholars of this scholarly, literary and spiritual family became famous throughout the subcontinent. In the said paper, the religious and social contributions of the famous intellectual and spiritual personalities of the Gangvi family will be reviewed. References will be taken from books, articles and interviews. Key Words: Gangvi, Islamic Scholars, Mianwali, subcontinent, Literary, Al Mufti al Azam, Manuscripts.